An Investigation on Metallic Ion Release from Four Dental Casting Alloys - F. Nejatidanesh; O. Savabi; A. Yazdanparast (Tehran University of Medical Sciences, 2005)
Statement of Problem: Element release from dental casting alloys into the oral environment is of clinical concern and is considered to be a potential health problem to all patients. Purpose: The aim of this study was to investigate the metallic ion release of four base metal alloys. Materials and Methods: Two Ni-Cr (Minalux and Supercast) and two Co-Cr alloys (Minalia and Wironit) were examined. Nine specimens of each type were prepared in 13×11×1.4 mm dimensions and each of the four alloys (3 specimens per group) were conditioned in artificial saliva at 37ْ c for one, three and seven days. The conditioning media were analyzed for element-release using Inductive Coupled Plasma Atomic Emission Spectrophotometer (ICPAES). Collected data were statistically analyzed using ANOVA and Duncan multiple range test (P< 0.05). Results: The greatest amount of element release was seen after seven days (134.9 ppb Supercast, 159.2 ppb Minalux, 197.2 ppb Minalia, and 230.2 ppb Wironit). There was a significant difference between the released elements from the alloys after the three conditioning times (p